2002
DOI: 10.1002/ijc.10492
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytochrome P450 (CYP) 2A6 gene deletion and CYP2E1 genotypes on gastric adenocarcinoma

Abstract: Cytochrome P450 (CYP) 2A6 and CYP2E1 are enzymes with a high ability to activate a nitrosamine, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK), to its potent and ultimate carcinogens. The polymorphic CYP2A6 and CYP2E1 have been implicated in increased susceptibility to certain malignancies. In our study, 120 Japanese patients with gastric adenocarcinoma and 158 healthy controls were compared for frequencies of CYP2A6 and CYP2E1 genotypes. The frequency with which the subjects carried homozygotes of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 28 publications
1
23
1
Order By: Relevance
“…On the other hand, other authors failed to demonstrate any statistically significant difference in the GSTM1 polymorphism distribution of gastric cancer patients and controls [24,26,32,36,52,55,56] . Several case-control studies also failed to find a significant association between the CYP2E1/PstI polymorphism and gastric cancer [23,24,26,34] . However, while Nishimoto et al [51] observed that the rare variant c2/c2 was associated with a reduced risk for gastric cancer in non-Japanese Brazilians, Wu et al [35] observed that the distribution of the c2/c2 genotype, detected by PstI or RsaI digestion, differed significantly between gastric cancer cases and controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, other authors failed to demonstrate any statistically significant difference in the GSTM1 polymorphism distribution of gastric cancer patients and controls [24,26,32,36,52,55,56] . Several case-control studies also failed to find a significant association between the CYP2E1/PstI polymorphism and gastric cancer [23,24,26,34] . However, while Nishimoto et al [51] observed that the rare variant c2/c2 was associated with a reduced risk for gastric cancer in non-Japanese Brazilians, Wu et al [35] observed that the distribution of the c2/c2 genotype, detected by PstI or RsaI digestion, differed significantly between gastric cancer cases and controls.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between GSTT1, GSTM1 and CYP2E1 gene polymorphisms and the risk for gastric cancer is not obvious. Many investigations were conducted on Asian populations [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] . The Brazilian population is characterized by heterogeneous ethnic groups, emphasizing the need to investigate the frequency of these metabolizing genes and their association with gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Kato et al, (1995) did not find any association between CYP2E1 RsaI genotype and stomach cancer. Tsukino et al, (2002);Park et al, (2003) and Darazy et al, (2011) also found no such association. In another study, Kato et al, (2011) reported that CYP2E1 RsaI polymorphisms do not influence the development of primary stomach cancer, but may do so in specific conditions, such as the remnant stomach after gastrectomy.…”
Section: Discussionmentioning
confidence: 88%
“…Usual case-control studies could provide the estimates for the final step (ie, literal carcinogenesis), when genotype frequency is different between gastric atrophy and gastric cancer, and the same among the uninfected, infected, and those with gastric atrophy. Table 5 lists the polymorphisms reported on gastric cancer risk, adopted from Gonzalez et al (Gonzalez et al, 2002) and recent studies (Ebert et al, 2005;Geddert et al, 2005;Li et al, 2005;Tsukino et al, 2002;Sugimoto et al, 2005;Gao et al, 2002;Wu et al, 2002;Goto et al, 2005;Lai et al, 2005a;Lee et al, 2004;Savage et al, 2004;Lai et al, 2005b;Lacasana-Navarro et al, 2006;Kim et al, 2005;Hamajima et al, 2002a;Duarte et al, 2005). The ORs are listed in case of being significant.…”
Section: Genetic Factors For Helicobacter Pylori-induced Gastric Carcmentioning
confidence: 99%
“…Biologically, the interactions of smoking, fresh vegetables/fruits and salty food with polymorphisms of carcinogen-metabolic enzyme and DNA repair enzymes are very plausible. cyclinD1 G870A Germany (Geddert, 2005) significant association (p=0.003) CYP1A1 Ile/Val China (Li, 2005) IleIle, CYP2C6 *1/*4 Japan (Tsukino, 2002) *1*1/*1*4, *4*4:3.14 (1.05-9.41) CYP2C19 *1/*2/*3 Japan (Sugimoto, 2005) * 1*1, no*1:1.98 (1.07-3.65)…”
Section: Genetic Factors For Helicobacter Pylori-induced Gastric Carcmentioning
confidence: 99%